Teachers' Roles in Relation to the Ownership Structure of a Faculty. (2016) - Arsenijević, Jasmina; Maljković, Milanka
Abstract: The purpose of this study is examining the roles university teachers assume in the educational process in relation to the ownership structure of their faculties: private or state-owned. The research was conducted in 2014 on Serbian faculties of engineering, on the sample of 545 students and 167 teachers. The method used on data obtained from the questionnaire was descriptive analysis (frequencies and percentages). Findings suggest that the roles of teachers employed at private faculties are more compatible to the new education paradigm than the roles assumed by the teachers on state-owned faculties. Conclusion that could be derived from those findings is that teachers on private faculties are abandoning traditional and non-flexible roles, and are turning to new models of teaching which focus on a proactive, constructivist role of the student and assign to the teacher the role of a mentor, more appropriate for digital era.